Dark tide ebook A novel. - Haynes, Elizabeth (2013)
"Chilling." — Associated Press "An intense psychological thriller." — Publishers Weekly From Elizabeth Haynes, author of the bestselling debut Into the Darkest Corner, comes a tense, gripping thriller about a woman caught in an underworld of corruption and murder. Genevieve has finally achieved her dream: to leave the stress of London behind and start a new life aboard a houseboat in Kent. She's found the perfect vessel: Revenge of the Tide. She already feels less lonely; as if the boat is looking after her. But the night of her boat-warming party, a body washes up, and to Genevieve's horror, she recognizes the victim. She isn't about to tell the police, though; hardly anyone knows about her past as a dancer at a private members' club, The Barclay. The death can't have anything to do with her. Or so she thinks... Soon, the lull of the waves against Revenge feels anything but soothing, as Genevieve begins to receive strange calls and can't reach the one person who links the present danger with her history at the club. Fearing for her safety, Genevieve recalls the moment when it all started to go wrong: the night she saw her daytime boss in the crowd at The Barclay... Dark, sexy, and exquisitely chilling, Dark Tide is another superb mystery from acclaimed rising star Elizabeth Haynes.